Shari’ah and ethical issues in the practice of the modified mudharabah family takaful model in Malaysia - Htay, Sheila Nu Nu; Syed, Ahmed Salman (International Association of Computer Science and Information Technology (I A C S I T), 2013)
Takaful is known as a Shari’ah compliant insurance in Muslim and non-Muslim countries. In this regard, Malaysia is a global leader in offering Islamic financial products and supports takaful. Due to the rapid growth of the takaful industry, the prevailing guidelines and regulations might not be adequate to capture the current needs of takaful operations. This has led to certain criticisms of the practice of the takaful industry from Shari’ah and ethical aspects. It is important to examine these issues because Shari’ah compliance and ethicality are the distinguishing factors that differentiate takaful from conventional insurance. If these issues are not resolved, participants and investors are set to lose confidence in the takaful industry. This paper focuses on the Shari’ah and ethical issues related to profit (surplus) sharing practice and the use of interest free loans in the modified mudarabah model used in family takaful products. The findings of this paper reveal the existence of unfavorable Shari’ah and ethical issues in the practice of takaful operations in Malaysia. As a result, the paper suggests that the regulators, Shari’ah advisors and industry players should revisit these issues in order to avoid reputational risk, Shari’ah compliant risk and early termination risk.